Effect of Planting Techniques and Leaf Cuttings on Seed Yield of Chinese Cabbage (Brassica campestris var. chinensis) - ARUN SHARMA; J.S. KANWAR; KULBIR SINGH; PARMINDER SINGH (Seed Research, 2026)
Studies were conducted at Seed Technology Farm, Punjab Agricultural University, Ludhiana to find out the effect of planting techniques and leaf cuttings on seed production of non-heading Chinese cabbage. There were 32 treatments comprising of eight planting techniques viz. direct seed sowing on flat bed (M,), direct seed sowing on flat bed followed by earthing up (M₂), direct seed sowing on ridges (M₂), direct seed sowing on ridges followed by earthing up (M₁), transplanting of seedlings on flat bed (M), transplanting of seedlings on flat bed followed by eatrthing up (M), transplanting of seedlings on ridges (M,), transplanting of seedlings on ridges followed by earthing up (Mg) as main plot treatment and four levels of leaf cuttings viz. no cutting (Co), one cutting (C₁), two cuttings (C₂) and three cuttings (C₂) as sub plot treatment and there were 3 replications. Among planting techniques, maximum number of branches per plant (10.9), number of pods per plant (1404.3), number of seed per pod (21.0) and seed yield per hectare (11.5 q/ha) were recorded in direct sown on ridges followed by earthing up (M₁) and minimum lodging per cent (4.2) was recorded in transplanted on ridges followed by earthing up (Mg) planting technique. Among leaf cutting treatments, maximum number of branches per plant (11.1) and number of pods per plant (1298.3) -were recorded in no leaf cutting treatment whereas maximum number of seed per pod (20.5) and seed yield per hectare (10.1 q/ha) were recorded in one leaf cutting treatment. Minimum lodging per cent (2.9) was observed in three-leaf cuttings treatment.